Factors Associated with Hypertension-Risk Eating Behavior in the Elderly in the Work Area of ​​the Mining Health Center: Analisis Pengelolaan Limbah Medis Padat B3 Saat Pandemi Covid-19 Di Rumah Sakit Bina Kasih Tahun 2022 - Rudi Miftah; Desvavri Desvavri; Nurvi Susanti; Sherly Vermita; Elmia Kursani; Aldiga Rienarti Abidin (Jurnal Olahraga dan Kesehatan (ORKES), 2022)
B3 solid medical waste is infectious waste that contains various pathogenic micro-organisms that can transmit disease, cause health and environmental problems, the production of solid medical waste at Bina Kasih Hospital Pekanbaru increased during the Covid-19 pandemic in 2019 reaching 7,560 kg while in 2017 2020 reached 9,780 kg. Management at Bina Kasih Hospital Pekanbaru City in 2022. This study used a qualitative method with observasion research instruments, in-depth interviews with 6 informants, namely the Director, the head of the general section, the PPI committee, the head of the emergency room, head of the midwifery room and cleaning service and, data processing techniques with triangulation of methods, sources and data, data analysis with reduction, data display and drawing conclusions. The results of the study were found that were not to standard, such as the reduction stage, namely there was no reuse of solid medical waste recycling. sorting stage, no symbols were found that matched the type of waste category. storage places found facilities and infrastructure that are still lacking. In the transportation stage, it was found that the cleaning service did not use complete PPE. The transportation processing stage from the 3rd party is carried out every 3 days. There are no competent environmental health personel in medical waste management B3 solid medical waste management is not in accordance with the standards of Regulation RI/NO.56/MENLHK-SETJEN/2015 and Regulation of the Minister of Health of the Republic of Indonesia/07/2019. Suggestions for Bina Kasih Hospital Pekanbaru should improve medical waste management to comply with the standards of Regulation RI/NO.56/MENLHK-SETJEN/2015 and Regulation of the Minister of Health of the Republic of Indonesia/07/2019.